The Relationship Between Integrated Marketing Strategies And Capital Attraction in banks (Field study in Syrian private commercial banks) (Journal of Hama University, 2021)
The aim of the research is to demonstrate the role of integrated marketing strategies (advertising, online marketing, personal selling, and direct marketing in attracting capital For Syrian private commercial banksThe descriptive approach was relied upon, and in order to test the hypotheses, the researcher relied on the questionnaire, and used electronic questionnaires with a number of members of the research sample, The researcher relied on the Likert quintuple scale in an attempt to obtain data related to the impact of integrated marketing strategies as one of the dimensions of integrated marketing in attracting capital to primary data in a database that was analyzed using SPSS version /20/.The researcher reached several conclusions, including: The advertisement used by the bank does not meet its objectives in marketing banking services, the bank does not rely on direct mail when receiving customer requests, the bank does not have a department for foreign investment, and the bank does not participate in global investment projects.